ANTI-CANCER PROPERTIES OF PHYTOCHEMICALS DERIVED FROM AZADIRACHTA INDICA: LITERATURE REVIEW - Saadah, Alfina Aisatus (Transpublika Publisher, 2022)
This study aims to assess the anti-cancer properties of phytochemicals derived from Azadirachta indica (neem), given the increasing prevalence of cancer and the need for safer and more effective therapies. Phytochemicals from Azadirachta indica have been reported to have potential as anti-cancer agents, but their mechanism of action is not fully understood. Therefore, this study was conducted to explore the anti-cancer potential of various phytochemicals extracted from Azadirachta indica. This study used literature review method supported by bibliometric analysis tools such as VOSviewer and Publish or Perish. The results showed that phytochemicals from Azadirachta indica have significant cytotoxic effects on cancer cells, as well as being able to induce apoptosis through intrinsic pathways. These results suggest that Azadirachta indica has the potential to be developed as an effective and safe anti-cancer therapeutic agent. Discussion of the results of this study highlights the importance of further development and clinical trials to validate these findings.